The Enhancement of Teacher Competency Through Assistance in Creating Augmented Reality-Based Interactive E-Modules at SMAN 10 Palembang - Ida Sriyanti; Leni Marlina; Agung Mataram; Muhammad Rudi Sanjaya; Selvia Mariska Syahputri; Rahma Dani; Muhammad Rama Almafie (Pascasarjana Universitas Mataram, 2025)
Educational transformation in the Industrial Revolution 4.0 era demands that teachers adapt to digital technology and develop innovation-based learning. However, the results of a preliminary survey indicated that a majority of teachers at SMAN 10 Palembang lacked skills in creating digital learning media and were unfamiliar with Augmented Reality (AR) technology. This community service activity aimed to improve teacher competence through mentoring in the creation of AR-based interactive e-modules as a 21st-century learning innovation. The implementation methods included socialization, technical training, a coaching clinic, and an evaluation of outcomes using a pre-test, post-test, and a participant satisfaction survey. Fifteen teachers actively participated in this activity. The paired sample t-test analysis revealed a significant increase between the pre-test (M = 47.00; SD = 7.75) and post-test scores (M = 91.67; SD = 4,87), with t = –18.506, p = 0.000 (p < 0.05). And the Cohen’s d = 9.35, categorized as a very large effect. This finding demonstrates that the mentoring program was effective in enhancing teacher competence in developing AR-based interactive e-modules. Furthermore, the results of the participant satisfaction survey reinforced the program's effectiveness. A total of 73.3% of participants stated they were